Aplicación del método montessori en el proceso de enseñanza y aprendizaje de educación inicial - Zambrano Gaibor, Jeniffer Leonor (2022)
The project established for scientific, methodological and experimental research, contains semblance and important aspects for the application and execution in the teaching-learning process, with Montessori didactic material for Initial Grade students; taking advantage of their ability to interpret, analyze one of the most accepted activities of children such as play-work in a simple way. The present project was applied in the Initial Grade of the "Francisco Huerta Rendon" Educational Unit of the Babahoyo Canton, after locating the situation of the problem by the observed investigation that is exposed in the infants; such as obtaining new learning, establishing direct objectives that can be carried out with the elaboration of the didactic material. It is supported in a theoretical and practical way in a scientific, methodological and experimental field, through reports, references and reports obtained from technical authors on the subject of research and inquiry; which was important for the creation of Montessori teaching material that stimulates the teaching-learning process in infants. The authenticity of the current activities is based on the deficiencies that were interpreted when observing the development in the daily day, due to the lack of adequate didactic material, which was an inconvenience for the teacher when stimulating the appropriate interests in the infants to undertake the process. Teaching-learning Reaching a certain conclusion in manufacturing and applying Montessori teaching materials, making using something different more effective, fun and considerable for infants.